Pengaruh Karakteristik Pekerjaan Dan Komunikasi Interpersonal Terhadap Kepuasan Kerja Pegawai Pada Distrik Navigasi Kelas 1 Palembang - Ariyanto, Sulpan; Kurniawan, M; Kurbani, Adie (Peneliti.net, 2024)
Abstract This study aims to identify and analyze the influence of job characteristics and interpersonal communication on employee job satisfaction in Class 1 Navigation District Palembang. The research methodology used in this study is associative quantitative method. The population of the study consists of 126 employees from Class 1 Navigation District Palembang. The sample was taken using a non-probability sampling technique (exhaustive sampling), with the entire population being included as the sample. Data analysis was conducted using simple regression analysis, multiple regression analysis, coefficient of determination analysis, as well as t-test and F-test. The results of the study indicate that job characteristics have a significant partial influence on job satisfaction in Class 1 Navigation District Palembang, as supported by hypothesis one (H1). Additionally, interpersonal communication also has a significant partial influence on employee job satisfaction in Class 1 Navigation District Palembang, in line with hypothesis two (H2). Furthermore, the results show that jointly, job characteristics and interpersonal communication have a significant influence on employee job satisfaction in Class 1 Navigation District Palembang, in accordance with hypothesis three (H3).